The Use of Inferior Vena Cava Ultrasonography to Assess Fluid Overload in Acute Lung Oedema in Severe Preeclampsia Patient - Pamrikso, Eko Setyo; Muhammad Husni Thamrin (HM Publisher, 2024)
Introduction: Accurate evaluation of volume status is essential for appropriate therapy because inadequate assessment of volume status can result in unnecessary administration of therapy, which can increase mortality. This study aimed to describe the use of inferior vena cava ultrasound in assessing fluid overload in severe preeclampsia patients. Case presentation: We report a 23-year-old female patient with a diagnosis of acute pulmonary oedema, and severe preeclampsia at G1P0A0 40 weeks gestation with complaints of shortness of breath. On physical examination, the patient appeared short of breath with RR 32 x/minute, fine wet crackles in both lung fields, SpO2 92% with NRM 15 L/m, HR 160 x/minute, lifting strength, CRT < 2 seconds, blood pressure 160/120 mmHg. This patient underwent emergency termination of pregnancy by C-section under general anesthesia rapid sequence induction followed by intensive care in the ICU. Management in the ICU this patient was given mechanical ventilation, midazolam sedation 0.05 mg/kg, analgesic morphine 10 mcg/kg, fluid restriction with a fluid balance target of (-)1000 ml/24 hours and given furosemide 10 mg/hour to reduce fluid overload so that fluid in the lungs can be reduced. Evaluation of fluid overload by IVC ultrasound. Conclusion: Acute pulmonary edema requires proper management to get a good outcome. Measurement of the diameter of the inferior vena cava (IVC) can also be used to assess fluid volume status. Lack of volume is assessed with an IVC diameter of <1.5 cm, while an IVC diameter of >2.5 cm indicates volume overload.